Preparation process of hydrogen isotope homogenization standard sample based on ion implantation of energy regulator

By using an ion beam implantation technology of an energy regulator in a zirconium alloy or zirconium oxide layer, uniform distribution of hydrogen isotopes is achieved, and the accuracy and uniformity of measuring hydrogen isotope content in the prior art is solved, and the preparation of standard samples and the correction of test results are achieved.

CN119804060APending Publication Date: 2025-04-11SICHUAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411948730.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

It is difficult to accurately measure the hydrogen isotope content in the zirconium alloy and zirconium oxide layer in the prior art, and conventional methods cannot achieve uniform distribution of hydrogen isotope components in the zirconium alloy or zirconium oxide layer.

Method used

Using ion beam implantation technology based on energy regulators, the energy and injection volume combination of hydrogen isotope ion beam is determined through simulation calculation to achieve uniform distribution of hydrogen isotopes in zirconium alloy or zirconium oxide layer.

Benefits of technology

The preparation of standard samples with uniform hydrogen isotope components in zirconium alloys or zirconia layers at low cost and high efficiency is achieved, providing a new technical approach to correct and compare advanced spectroscopy and mass spectrometry test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804060A_ABST
    Figure CN119804060A_ABST
Patent Text Reader

Abstract

The invention discloses a standard sample preparation process for uniformly injecting hydrogen isotopes into a fuel cladding zirconium alloy or zirconium oxide layer. The preparation method of the standard sample with the uniform hydrogen isotope content of the zirconium alloy or the zirconium oxide layer specifically comprises the following three steps: step 1, preparing the standard sample according to the requirements of the hydrogen isotope content in the zirconium alloy or the zirconium oxide layer and the thickness of a uniform distribution layer; calculating the energy and fluence combination mode of the two or more hydrogen isotope ion beams by adopting simulation software; 2, selecting the material type and thickness of the foil type energy regulator by adopting analog computation; and 3, according to the calculated hydrogen isotope ion beam energy and fluence results, performing hydrogen isotope ion beam injection on the determined foil type energy spectrum stretcher and the zirconium alloy or zirconium oxide layer to be injected to obtain a standard sample with uniform hydrogen isotope content. According to the process, the standard sample with uniform hydrogen isotope components in the fuel cladding zirconium alloy or the zirconium oxide layer can be prepared with low cost and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparing standard samples with uniform hydrogen isotope composition in the oxide layer of the zirconium alloy cladding of nuclear fuel reactors. In order to more easily analyze the hydrogen isotope content in the zirconium alloy or zirconium oxide sample to be tested, the present invention specifically relates to a computational simulation method for determining the combined energy and injection amount of hydrogen isotope ion beams, and at the same time, regulating the uniform distribution of hydrogen isotope composition in the zirconium alloy or zirconium oxide layer through the action of an energy regulator. Based on the simulation results, a standard sample with uniform hydrogen isotope distribution is obtained in the zirconium alloy or zirconium oxide in the submicron or micron depth range by using ion implantation technology. Background Art

[0002] Nuclear energy has potential advantages in solving the problem of energy shortage due to its clean, economical and reliable characteristics. Zirconium alloy has the characteristics of small cross-sectional area for thermal neutron absorption, strong resistance to neutron irradiation, excellent mechanical properties, and resistance to high temperature and high-pressure water vapor corrosion. It is widely used as a cladding material for nuclear fuel. During the operation of the reactor, the zirconium alloy cladding tube will react with the cooling medium. Part of the hydrogen produced by the corrosion of the material will become hydrogen and enter the cooling medium, and the other part will be absorbed by the zirconium cladding. When the hydrogen absorbed by the zirconium cladding exceeds its solid solubility limit, the excess hydrogen will precipitate in its matrix in the form of hydride. Hydride is a brittle phase, and its presence will reduce the toughness of the zirconium alloy and seriously affect the safe and stable operation of the reactor. In recent years, the study of the effect of hydrogen on zirconium alloy has gradually received attention. Therefore, it is urgent to study the effect of different hydrogen contents on the mechanical properties of zirconium cladding in depth and comprehensively; on the other hand, zirconium is an active metal, and zirconium alloy will undergo an oxidation reaction of Zr+2H2O→ZrO2+2H2 in high-temperature water or steam. The reaction is slow at first. When the oxide film thickness reaches 2-3 microns, the corrosion rate suddenly increases. The reason is that the oxide film thickens and the stress increases, causing cracks in some oxide films. Before the turning point, the oxide film is black and shiny, and the structure is ZrO 2-n(n<0.05) monoclinic crystals, which are dense and firmly attached to the metal surface and have protective properties. Under the operating conditions of nuclear reactors, the water side corrosion of the fuel cladding under pressurized water reactor conditions is generally manifested as uniform corrosion, and under boiling water reactor conditions, there is a phenomenon of nodular corrosion, which is characterized by the appearance of round raised white spots on the surface of the oxide film after the oxide film grows uniformly to a certain thickness. The corrosion depth can exceed 100μm and the distribution varies. With the development of nodular corrosion, this nodular spot will grow and connect into one piece, forming a loose and easy to fall off gray-white oxide film. Various models have been proposed for the nucleation and growth process of nodular spots, including the hydrogen aggregation model of Japanese scholar Kuwae, Cheng's alloy element depletion theory, and the nucleation and growth model proposed by Chinese scholar Zhou Bangxin, etc. Kuwae et al. believed that H2 formed during the oxidation of zirconium alloys accumulates at the interface between the matrix and the oxide film. When the pressure caused by the accumulated H2 exceeds the fracture strength of ZrO2, the oxide film ruptures and forms boil-like corrosion. Furthermore, for heavy water reactors, the design life of pressure tubes is up to 30 years, which is about 30 times that of typical zirconium cladding alloys (12-18 months), but its hydrogen isotope content requirement at the end of its life is comparable to that of other zirconium alloy claddings. Therefore, in order to meet the requirements of Zr-Nb for heavy water reactor pressure tubes, 2.5 The corrosion resistance and hydrogen absorption resistance of the alloy meet the design requirements. Pre-oxidation film treatment on the surface of zirconium alloy is one of the many surface modification methods. According to limited information, the pre-film treatment of the pressure pipe is to form a protective bright black pre-film on the surface while performing stress relief treatment in water vapor. Zr-Nb 2.5 The main component of the pre-film on the alloy surface is dense monoclinic zirconium oxide (ZrO 2-n (n<0.05)) and a small amount of tetragonal zirconium oxide phase (ZrO2). It can be seen that for the existing nuclear reactor service conditions, the oxide layer (ZrO x ) determines the overall hydrogen absorption capacity of the zirconium alloy cladding. Existing studies have shown that the oxide layer will prevent hydrogen migration and protect the zirconium alloy cladding to a certain extent. However, it is difficult to accurately measure the hydrogen isotope content in zirconium alloys and zirconium oxide layers using conventional characterization methods. In this context, how to accurately obtain zirconium alloy and zirconium oxide samples with different hydrogen contents has become the primary task for subsequent mechanical property evaluation.

[0003] In order to obtain zirconium alloys with different hydrogen contents, the correct hydrogenation method should be selected first, and then a reasonable detection method should be selected to evaluate the hydrogen content. At present, the main hydrogenation methods for zirconium alloys are electrolytic hydrogenation and gaseous hydrogenation. The hydrogenation temperature of the electrolytic hydrogenation method is low (60 ℃), and the hydrogenation time is long, generally requiring 8-24 h. The diffusion rate of hydrogen atoms is slow at low temperatures, and it is easy to form a layer of hydride on the surface of the sample, thereby affecting the uniform distribution of hydrogen content. In contrast, the gaseous hydrogenation method has the characteristics of high hydrogenation temperature (450 ℃), fast hydrogenation rate (10 min), and uniform distribution of hydrogen content, and has been widely used in the hydrogenation treatment of zirconium alloys. However, zirconium alloys cannot avoid the presence of zirconium oxide film on the surface of zirconium alloys in high-temperature water or steam service environments. Therefore, the method of using gas phase hydrogenation isotope method to study and evaluate the distribution and diffusion behavior of hydrogen isotopes in reactor zirconium alloys and zirconium oxide layers is also greatly limited.

[0004] At present, the commonly used methods for detecting the hydrogen content in zirconium alloy and zirconium oxide layer are weighing method, metallographic method, chemical analysis method, spectroscopy (laser Raman spectroscopy, laser induced breakdown spectroscopy, Fourier transform infrared spectroscopy), gas chromatography and mass spectrometry (spark source mass spectrometry, secondary ion mass spectrometry, thermal vacuum extraction-quadrupole mass spectrometry) etc. Among them, the metallographic method is to evaluate the hydrogen content in zirconium alloy by observing the number of hydrides after hydrogen permeation. This method is more intuitive, and the measured hydrogen content is related to the mechanical properties, but the test results have large errors or low confidence, and cannot be accurately quantified; the weighing method is to calculate the hydrogen content of the sample by using the increase in mass after hydrogen absorption. When the metallographic method is used to calculate the hydrogen content, it is affected by the mass of the sample itself and the accuracy of the analytical balance. Its accuracy is insufficient and the error is large, but this method can reflect the overall hydrogen content of the sample and is easy to operate; the commonly used chemical analysis method is the inert gas melting infrared absorption method, the principle of which is to melt the sample at high temperature to precipitate hydrogen atoms and react with copper oxide to generate H2O. At a wavelength of 7.0 μm, the absorption of infrared radiation by H2O and its concentration follow the Lambert-Beer law. A photodetector can be used to detect the change in the light intensity of the infrared absorption cell, thereby converting its hydrogen content. This method has high detection accuracy, but is limited by the sampling location and has great limitations. It can only reflect the hydrogen content at a certain point, not the hydrogen content of the entire sample, and in the case of uneven hydrogen content, especially when hydride is precipitated, the detection results have great volatility. In recent years, laser-induced breakdown spectroscopy (LIBS) and mass spectrometry (such as secondary ion mass spectrometry (SIMS) and thermal desorption mass spectrometry (TDS)) have high precision and accuracy. In particular, LIBS and SIMS can detect the hydrogen isotope content of the sample along the thickness and depth direction, have spatial resolution, and the analysis and testing methods are relatively reliable and standard. However, the accuracy and reliability of the test results of laser induced breakdown spectroscopy and mass spectrometry (especially secondary ion mass spectrometry) lack the calibration and comparison of hydrogen isotope standard samples recognized by the industry, making it difficult to accurately measure the hydrogen isotope content in the zirconium alloy oxide layer. Constructing a zirconium oxide layer sample with known hydrogen isotope (hydrogen (H) or deuterium (D)) content and distribution in the oxide region as a standard sample (referred to as "standard sample") can easily obtain the hydrogen isotope content and distribution of the sample to be tested, and quantitatively establish the concept of this barrier that controls corrosion and hydrogen absorption performance. In order to more easily analyze the sample to be tested, the content distribution of hydrogen isotopes in the standard sample must be uniform within a certain depth range. Summary of the invention

[0005] The present invention discloses a standard sample preparation process for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide layer of fuel cladding based on energy regulator ions. The preparation of the standard sample with uniform hydrogen isotope content in zirconium alloy or zirconium oxide layer of the present invention is specifically divided into three steps: the first step is to use simulation software to calculate the energy and injection combination of two or more beams of hydrogen isotope ion beams required according to the requirements of hydrogen isotope content and thickness of uniformly distributed layer in zirconium alloy or zirconium oxide layer; the second step is to use simulation calculation to select the material type and thickness of foil energy regulator; the third step is to implant hydrogen isotope ion beams into the determined foil energy spectrum expander and zirconium alloy or zirconium oxide layer to be implanted according to the above calculated hydrogen isotope ion beam energy and injection results to obtain a standard sample with uniform hydrogen isotope content. The process of the present invention can prepare standard samples with uniform hydrogen isotope content in zirconium alloy or zirconium oxide layer of fuel cladding at low cost and high efficiency. It provides a new technical approach for calibrating and comparing the accuracy and reliability of test results of advanced spectroscopy and mass spectrometry (especially secondary ion mass spectrometry).

[0006] The technical solution provided by the present invention is: a standard sample preparation technology for uniformly implanting hydrogen isotopes in a zirconium alloy or zirconium oxide layer of a fuel cladding based on energy regulator ions, characterized in that the technology comprises the following steps: a. Zirconium alloy for core: Zr-4 or Zr-Nb 2.5 Alloy, etc.; the zirconium oxide layer is obtained by physical vapor deposition methods such as magnetron sputtering or evaporation, or by direct oxidation annealing of zirconium alloy; b. According to the requirements of the specific standard sample for the hydrogen isotope content and the thickness of the uniformly distributed layer, simulate and calculate the energy and injection combination of two or more hydrogen isotope ion beams required; c. Combined with step a, the material type and thickness of the foil energy regulator are selected through simulation calculation; d. placing the foil energy regulator and the zirconium alloy or zirconium oxide sample material to be injected into the injection vacuum target chamber of the accelerator; e. Performing ion beam implantation on the zirconium alloy or zirconium oxide sample according to the energy and injection data of the hydrogen isotope ion beam obtained in step c to obtain a standard sample with uniform hydrogen isotope concentration; The standard sample preparation technology based on uniform ion implantation of hydrogen isotopes in the above-mentioned zirconium alloy or zirconium oxide is characterized in that the zirconium alloy is Zr-4 alloy or Zr-Nb 2.5 alloy, etc., with uniform grain size distribution; the zirconium oxide is ZrO 2-X layer, the value of x is <0.05, ZrO 2-X The oriented monoclinic phase accounts for more than 95% of the layer, the grain size is evenly distributed, the thickness is 550-600 nm, and it can be obtained by vapor deposition technology or oxidation annealing and other processes.

[0007] The above-mentioned standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide based on energy regulator ions in fuel cladding is characterized in that the calculation software used in step a and step b can be open source calculation software, such as Stopping and Range of Ions in Matter (SRIM), or any other software that can be used to calculate the ion depth distribution of energetic ion beam implantation; The above-mentioned standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide of fuel cladding based on energy regulator ions is characterized in that, in the steps a and b, by adjusting the energy and injection amount of two or more hydrogen isotope ion beams, the uniformity deviation of hydrogen isotope ion beam implantation is formed to be less than 5%; The above-mentioned standard sample preparation technology based on uniform implantation of hydrogen isotopes by energy regulator ions in zirconium alloy or zirconium oxide of fuel cladding is characterized in that the foil-type energy regulator material in step b can be a single material (such as various metal foils), a compound material, an alloy material or a polymer material; the type and thickness of the foil-type energy regulator are determined depending on the depth range of the uniform hydrogen isotope concentration layer required by the standard sample; The above-mentioned standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide of fuel cladding based on energy regulator ions is characterized in that, in the step b, the type and thickness of the foil energy regulator are determined depending on the energy of the incident hydrogen isotope ion beam selected in step S1; The above-mentioned standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in fuel cladding based on energy regulator ions is characterized in that the vacuum degree of the irradiation target chamber in step c is equal to or less than 10 -5 Pa; a foil energy regulator is placed in front of the zirconium alloy or zirconium oxide sample to be implanted; The above-mentioned standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions is characterized in that the accelerator in step d can be an electrostatic accelerator, an ion implanter or other equipment that can accelerate charged particles and obtain specific energy; The above-mentioned standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions is characterized in that, in the ion beam implantation process in step e, the implantation order of ion beams with different energies is not distinguished; The above-mentioned standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide of fuel cladding based on energy regulator ions is characterized in that the ion beam implantation treatment in step e and the hydrogen isotope ion beam implantation can be carried out at room temperature.

[0008] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts a standard sample preparation technology based on uniform ion implantation of hydrogen isotopes in zirconium alloy or zirconium oxide, characterized in that the zirconium alloy is Zr-4 alloy or Zr-Nb 2.5 alloy, etc., with uniform grain size distribution; the zirconium oxide is ZrO 2-X layer, the value of x is <0.05, ZrO 2-X The oriented monoclinic phase in the layer accounts for more than 95%, the grain size is evenly distributed, and the thickness is 550-600 nm. It can be obtained by vapor deposition technology or oxidation annealing and other processes, laying the foundation for subsequent hydrogen isotope injection and measurement; 2. The present invention discloses a standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide of fuel cladding based on energy regulator ions, characterized in that by adjusting the energy and injection amount of two or more hydrogen isotope ion beams, the uniformity deviation of hydrogen isotope ion beam implantation is less than 5%; the foil energy regulator material used can be a single material (such as various metal foils), a compound material, an alloy material or a polymer material; the type and thickness of the foil energy regulator are determined depending on the depth range of the uniform hydrogen isotope concentration layer required by the standard sample; the operation is convenient and controllable, and can be implemented at room temperature, with mature technology, low cost, strong process stability, stability and reliability of the prepared hydrogen isotope standard, and the inhomogeneity of gas and electrolytic hydrogenation isotopes in the oxide layer is avoided; 3. The standard sample based on the uniform implantation of hydrogen isotopes by energy regulator ions in the zirconium alloy or zirconium oxide layer of the fuel cladding of the present invention can be used to calibrate a one-time spectroscopic determination method such as (inert gas melting infrared absorption method), and can also be used to calibrate the results of spectroscopic and mass spectrometric methods (especially secondary ion mass spectrometry) of multiple measurement results. The standard sample based on the uniform implantation of hydrogen isotopes by energy regulator ions in the zirconium alloy or zirconium oxide layer has a stable structure and reliable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 Depth profile of 125 keV D+ implanted into a 1 μm ZrO2 / Si film.

[0010] Figure 2 This is the ion energy distribution of 1.7 MeV D ions after energy reduction and broadening by the energy regulator.

[0011] Figure 3 The depth distribution of D atoms after a 1.7 MeV D ion beam is implanted into a 1-micron ZrO2 / Si film after the ion energy is broadened by an energy regulator.

[0012] Figure 4 Figure 3 shows the depth distribution of D atoms formed by implanting two beams of MeV D ions into a 1 μm ZrO2 / Si film.

[0013] Figure 5 Three beams of MeV D ions were implanted into 1 μm ZrO 2 / Depth distribution of D atoms formed in Si film. DETAILED DESCRIPTION

[0014] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but this does not mean any limitation on the protection content of the present invention.

[0015] The materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. A standard sample preparation technology for uniformly implanting hydrogen isotopes in a zirconium alloy or zirconium oxide layer of a fuel cladding based on an energy regulator ion, characterized in that the zirconium alloy is a nuclear Zr-4 or Zr-Nb 2.5 Alloy, etc.; the zirconium oxide layer is obtained by physical vapor deposition such as magnetron sputtering or evaporation, or by direct oxidation annealing of the zirconium alloy; in a preferred embodiment, the ZrO 2-X In the layer, the value of x is <0.05, the oriented monoclinic phase accounts for more than 95%, the grain size is evenly distributed, and the thickness is 550-600 nm. The specific implementation includes the following embodiments: Example 1

[0016] S0, according to the composition, ZrO is prepared by powder metallurgy technology 2-X , and obtain ZrO2 target; raw material powder with a purity higher than 99.9% is used to prepare a 50.8 mm diameter round sheet target by powder metallurgy technology, and the purity of the target is above 99.9%. The purity of ZrO2 target reaches 99.94%. For the single crystal Si substrate, acetone and ethanol are used as solvents for degreasing and oil removal in an ultrasonic instrument; then it is cleaned with deionized water, dried and placed in the vacuum chamber of the magnetron sputtering instrument, and the vacuum system is used to make the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa; keep the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa conditions, the single crystal Si substrate was back-sputtered and cleaned, the back-sputtering bias voltage was -700 V; the back-sputtering gas was argon; the back-sputtering pressure in the vacuum chamber was 5 Pa, and the back-sputtering cleaning lasted for 10 minutes; the vacuum degree in the vacuum chamber was kept <4.0×10 -4Pa conditions, the target was cleaned by pre-sputtering for 15 min, where: the pre-sputtering power of the ZrO2 target was 200 W; the pre-sputtering bias was -100 V; the pre-sputtering gas was argon; the pre-sputtering pressure in the vacuum chamber was 0.38 Pa; and ZrO was then deposited under uninterrupted vacuum conditions. 2-X layer, the argon flow rate was 25 sccm, the sputtering power was 200 W, the bias voltage was -50 V; the deposition time was 4 h, and the working pressure during sputtering was 0.38 Pa; the deposited ZrO X The film was finally annealed at 700 ℃-800 ℃ in vacuum for 0.5 h to obtain ZrO with a monoclinic phase ratio of more than 95% and uniform grain size distribution. 2-X (X<0.05) zirconia film.

[0017] S1. According to the requirements of the specific standard sample for the hydrogen isotope content and the thickness of the uniformly distributed layer, simulate and calculate the energy and injection combination of the required single beam, two beams or multiple beams of hydrogen isotope ion beams; Figure 1 To calculate the ion depth distribution of 125 keV D ions implanted into a 1 micron ZrO2 / Si film, it can be seen that the implantation is normally distributed, forming a very strong "Bragg" peak. The implanted ions will accumulate in a certain area of ​​the film, while the content of hydrogen isotopes in other areas is almost zero, and it is impossible to achieve a uniform distribution of deuterium concentration; Figure 2 To calculate the ion energy distribution of 1.7 MeV D ions after energy reduction and broadening through a 25 μm pure aluminum energy regulator; Figure 3 In order to calculate the depth distribution of D atoms after a 1.7 MeV D ion beam was broadened by an energy regulator and then implanted into a 1 μm thick ZrO2 film, a significant concentration broadening was obtained; to achieve a relatively uniform hydrogen isotope distribution in depth, a single MeV ion beam broadening is not sufficient to meet the conditions. Figure 3 The depth distribution of D atoms injected into the ZrO2 film after the 1.7 MeV D ion beam was broadened by the energy regulator. Compared with the 125 keV monoenergetic D ion implantation, although the depth distribution of D has been broadened a lot, almost covering the entire zirconia film area, its depth distribution is still uneven; using two or more MeV ion beams with different initial energies will form energy broadening with different energy distributions after passing through the energy regulator. Reasonable adjustment of the initial energy and ion beam injection of these ion beams can distribute the number of deposited ions at different depths of the ZrO2 film, thereby achieving a uniform depth distribution of D atoms within the required depth range of the ZrO2 film. Figure 4 and Figure 5The depth distribution of D atoms implanted into a 1 μm ZrO2 / Si film by MeV D ion beams with two and three different initial energies. In both cases, the maximum deviation of the D atom content within a depth range of 600 nm relative to its average value is less than 5% and 2%, respectively.

[0018] S2. Based on the simulation results of step S1, the material of the foil energy regulator is selected to be pure aluminum with a thickness of 25 microns.

[0019] S3, place the pure aluminum foil energy regulator and the zirconium oxide sample material to be injected into the injection vacuum target chamber of the accelerator, and the vacuum degree is less than 2×10 -5 Pa.

[0020] S4. Perform ion beam implantation on the zirconium alloy or zirconium oxide sample according to the energy and injection data of the hydrogen isotope ion beam obtained in step S1 to obtain a standard sample with uniform hydrogen isotope concentration. Example 2

[0021] S0. The zirconium alloy substrate is ground and polished with water sandpaper of different roughness (80 mesh, 220 mesh, 400 mesh, 800 mesh, 1200 mesh, 2000 mesh) in turn. In this embodiment, the zirconium alloy is Zr-2.5Nb alloy. Then, acetone and ethanol are used as solvents to degrease and clean in an ultrasonic instrument; then, it is cleaned with deionized water, dried, and placed in a vacuum chamber. The vacuum system is used to make the vacuum degree in the vacuum chamber less than 4.0×10 -3 Pa, oxygen / argon gas was introduced with an oxygen partial pressure of 1 / 10, and annealing was performed at 700 ℃-800 ℃ for 2 h to obtain a monoclinic phase with a proportion of more than 95%, and a uniformly distributed ZrO grain size was obtained on the surface of the zirconium alloy. 2-X (X<0.05) zirconia film.

[0022] S1. According to the requirements of the specific standard sample for the hydrogen isotope content and the thickness of the uniformly distributed layer, simulate and calculate the energy and injection combination of two or more hydrogen isotope ion beams; using two or more MeV ion beams with different initial energies, after passing through the energy regulator, different energy distributions will be formed. By reasonably adjusting the initial energy and ion beam injection of these ion beams, the number of deposited ions can be distributed at different depths of the ZrO2 film, thereby achieving a uniform D atom depth distribution within the required ZrO2 film depth range. Figure 4 and Figure 5 The depth distribution of D atoms implanted into a 1 μm ZrO2 / Si film by MeV D ion beams with two and three different initial energies. In both cases, the maximum deviation of the D atom content within a depth range of 600 nm relative to its average value is less than 5% and 2%, respectively.

[0023] S2. Based on the simulation results of step S1, the material of the foil energy regulator is selected to be pure aluminum with a thickness of 25 microns.

[0024] S3, place the pure aluminum foil energy regulator and the zirconium oxide sample material to be injected into the injection vacuum target chamber of the accelerator, and the vacuum degree is less than 2×10 -5 Pa.

[0025] S4. Perform ion beam implantation on the zirconium alloy or zirconium oxide sample according to the energy and injection data of the hydrogen isotope ion beam obtained in step S1 to obtain a standard sample with uniform hydrogen isotope concentration. Example 3

[0026] S0. The zirconium alloy substrate is ground and polished with water sandpaper of different roughness (80 mesh, 220 mesh, 400 mesh, 800 mesh, 1200 mesh, 2000 mesh) in turn. In this embodiment, the zirconium alloy is Zr-2.5Nb alloy. Then, acetone and ethanol are used as solvents to degrease and clean in an ultrasonic instrument; then, it is cleaned with deionized water, dried, and placed in a vacuum chamber. The vacuum system is used to make the vacuum degree in the vacuum chamber less than 4.0×10 -3 Pa, and annealed at 700 ℃-800 ℃ in vacuum for 2 h to remove the residual hydrogen isotopes in the zirconium alloy.

[0027] S1. According to the requirements of the specific standard sample for the hydrogen isotope content and the thickness of the uniformly distributed layer, simulate and calculate the energy and injection combination of two or more hydrogen isotope ion beams; use two or more MeV ion beams with different initial energies, which will form energy broadening with different energy distributions after passing through the energy regulator. Reasonable adjustment of the initial energy and ion beam injection of these ion beams can distribute the number of deposited ions at different depths of the zirconium alloy film, thereby achieving a uniform D atom depth distribution within the required depth range of the zirconium alloy film.

[0028] S2. Based on the simulation results of step S1, the material of the foil energy regulator is selected to be pure aluminum with a thickness of 30 microns.

[0029] S3, place the pure aluminum foil energy regulator and the zirconium oxide sample material to be injected into the injection vacuum target chamber of the accelerator, and the vacuum degree is less than 2×10 -5 Pa.

[0030] S4. Perform ion beam implantation on the zirconium alloy or zirconium oxide sample according to the energy and injection data of the hydrogen isotope ion beam obtained in step S1 to obtain a standard sample with uniform hydrogen isotope concentration.

Claims

1. A standard sample preparation technique for uniformly implanting hydrogen isotopes in a zirconium alloy or zirconium oxide layer of a fuel cladding based on energy regulator ions, characterized in that: The technique includes the following steps: S0, zirconium alloy for core Zr-4 or Zr-Nb 2.5 Alloy, etc.; the zirconium oxide layer is obtained by physical vapor deposition methods such as magnetron sputtering or evaporation, or by direct oxidation annealing of zirconium alloy; S1. According to the requirements of the specific standard sample for the hydrogen isotope content and the thickness of the uniformly distributed layer, simulate and calculate the energy and injection combination of two or more hydrogen isotope ion beams required; S2, combining step S0, selecting the material type and thickness of the foil energy regulator through simulation calculation; S3, placing the foil energy regulator and the zirconium alloy or zirconium oxide sample material to be injected into the injection vacuum target chamber of the accelerator; S4. Perform ion beam implantation on the zirconium alloy or zirconium oxide sample according to the energy and injection data of the hydrogen isotope ion beam obtained in step S2 to obtain a standard sample with uniform hydrogen isotope concentration.

2. A standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: The zirconium alloy is Zr-4 alloy or Zr-Nb 2.5 alloy, etc., with uniform grain size distribution; the zirconium oxide is ZrO 2-X layer, the value of x is <0.05, ZrO 2-X The oriented monoclinic phase accounts for more than 95% of the layer, the grain size is evenly distributed, the thickness is 550-600 nm, and it can be obtained by vapor deposition technology or oxidation annealing and other processes.

3. A standard sample preparation technology for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: The calculation software used in step S1 and step S2 may be open source calculation software, such as Stopping and Range of Ions in Matter (SRIM), or any other software that can be used to calculate the ion depth distribution of energetic ion beam implantation.

4. A standard sample preparation technique for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: In step S1 and step S2, by adjusting the energy and injection amount of two or more hydrogen isotope ion beams, the uniformity deviation of hydrogen isotope ion beam implantation is less than 5%.

5. A standard sample preparation technique for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: The material of the foil type energy regulator in step S2 can be a single material (such as various metal foils), a compound material, an alloy material or a polymer material; the type and thickness of the foil type energy regulator depends on the depth range of the uniform hydrogen isotope concentration layer required by the standard sample.

6. A standard sample preparation technique for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: In step S2, the type and thickness of the foil energy adjuster are determined based on the energy of the incident hydrogen isotope ion beam selected in step S1.

7. A standard sample preparation technique for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: The vacuum degree of the irradiation target chamber in step S3 is equal to or less than 10 -5 Pa; a foil energy regulator is placed in front of the zirconium alloy or zirconium oxide sample to be implanted.

8. A standard sample preparation technique for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: The accelerator in step S3 may be an electrostatic accelerator, an ion implanter or other equipment that can accelerate charged particles and obtain specific energy.

9. A standard sample preparation technique for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: In the ion beam implantation process in step S4, the implantation order of ion beams with different energies is not distinguished.

10. A standard sample preparation technique for uniformly implanting hydrogen isotopes in zirconium alloy or zirconium oxide in a fuel cladding based on energy regulator ions according to claim 1, characterized in that: The ion beam implantation process in step S4 may be performed at room temperature.

Citation Information

Patent Citations

  • Sb ion implantation doping and annealing activation method for ZnO single crystal

    CN102691108A

  • Method for determining helium concentration depth distribution in metal material by using radio frequency glow discharge spectrometer

    CN111562253A

  • Semiconductor substrate reforming method and semiconductor device using the same

    JP2004079912A

  • Ion tilting implantation method

    KR1020090067905A

  • A method for hydrogen ion implanting into Zirconium alloy using proton beam

    KR1020100069256A